PENGARUH TINGKAT INFLASI, KURS DAN SUKU BUNGA TERHADAP INDEKS SAHAM DI JAKARTA ISLAMIC INDEX (JII) - Siti Aisah; Nihayatul Masykuroh; Moch Indrajit Roy (Tazkiya, 2019)
The study aims to analyze: 1) the influence of stock index on Jakarta Islamic Index (JII), 2) the influence of inflation, 3) the influence of exchange rate, 4) the influence of interest rate. This research uses the type of time series data with the nature of quantitative research, which thhis study uses monthly data from 2016-1018. The population used, namely the company (issuer) registered with JII and calculates the average value of the share price, so that it can get the JII stock index, determination of number of sample by using saturated sampling. Data source is secondary data were collected by browsing of financial statement OJK and website Indonesian Banking. The result of this study are: 1) Inflation does not significantly influence the JII stock index, 2) exchange rate have a significantly effect on JII stock index, 3)interest rate does not significantly influence the JII stock index